Identitas Kesukuan dan Multikulturalisme Etnis Mahasiswa Makassar Dalam Membangun Relasi Sosial Inklusif di Daerah Istimewa Yogyakarta - Rianda Usmi; Dasim Budimansyah; Rahmat Rahmat; Iim Siti Masyitoh; Beti Indah Sari (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The plurality of religions, ethnicities, languages, and cultures in Indonesia is prone to potential conflict, especially regarding intolerance and violence. The Makassar ethnic group is known to have a strong sense of tribalism towards their ethnicity. This study aims to (1) discribe of the tribal or ethnic identity of Makassar students in Yogyakarta; (2) to reveal the multiculturalism of Makassar students, the strength of their recognition and the depth of their respect for cultural diversity other ethnic’s cultures. This research uses a qualitative approach with a ethnography method. The subjects of this study were South Sulawesi students living in the Makassar Dormitory (Bawakaraeng and Lantimojong Dormitories) in the Special Region of Yogyakarta. Data collection techniques included in-depth interviews, documentation, and observation. Data validity was tested using source triangulation. The analysis technique used was inductive data analysis. The results of this study yielded the following findings: (1) the ethnic awareness embedded in Makassar students is very high, as demonstrated by their sense of pride and belonging to their ethnic group as a legacy of their ancestors; (2) the multiculturalism of Makassar students towards other ethnic/tribal cultures is relatively high, as seen from the type of multiculturalism they embrace, namely critical-interactive. The findings of this study, it can be concluded that the ethnic identity of Makassar students in Yogyakarta does not give rise to exclusivism. On the contrary, it is consistent with the practice of critical-interactive multiculturalism, which means that the Makassar ethnic group builds inclusive social relations in the Yogyakarta community.